Performance evaluation and comparison of commonly used optimization algorithms for natural gas liquefaction processes - Sun, Heng; Geng, Jinliang; Na, Fengyi; Rong, Guangxin; Wang, Chao (Energy reports, 2022)
The genetic algorithm (GA), particle swarm optimization (PSO) algorithm, and BOX algorithm have been used in natural gas liquefaction process optimization. Three algorithms all can find a solution by adopting different strategies and computational efforts. Therefore, it is necessary to compare their performance. This article presents a performance comparison of the GA, PSO, and BOX algorithms for the optimization of four natural gas mixed refrigerant liquefaction processes. The results show that PSO has the best optimization performance, reducing the specific energy consumption (SEC) to 0.3233 kWh/kg, 0.2351 kWh/kg, 0.2489 kWh/kg, and 0.2427 kWh/kg for single mixed refrigerant (SMR), dual mixed refrigerant (DMR), propane pre-cooling mixed refrigerant (C3MR), and mixed fluid cascade (MFC), respectively. Furthermore, PSO also improved the exergy efficiency of the four processes to 35.34%, 48.59%, 45.90%, and 47.07%. The composite curve analysis shows that the heat transfer efficiency of the heat exchanger optimized by PSO is more efficient. The study also discovered that the total optimization performance of PSO and GA is better than BOX algorithm, and the GA optimization performance is second only to PSO. This research would greatly assist process engineers in making the right decision on process optimization to overcome energy efficiency challenges. •Four MR processes are optimized by GA, PSO and BOX algorithms and the performance is analyzed and compared.•Process optimization by PSO gets a significant improvements in specific energy consumption and exergy efficiency.•The convergence accuracy and stability of the PSO are higher than the GA, while the unit computation time is reversed.•The PSO has the best optimization performance, followed by the GA and BOX algorithm.